Medical laboratory professional’s week in Rwanda: a field report from the Simbi and Maraba communities - Gashema, Pierre; Iradukunda, Patrick G.; Tumusiime, Musafiri; Harelimana, Jean D.; Rutayisire, Gad; Nyakatswau, Stuart T.; Samjeh, Oswald; Muhwezi, Andrew; Mwikarago, Ivan E.; Gitema, Fiston; Ndoricyimpaye, Ella L.; Rugimbanya, Pierre; et al. (International Journal Of Community Medicine And Public Health, 2021)
Background: In response to the need for interventions that facilitate the accessibility of medical services in poor communities, an outreach activity was organized in semi-rural areas of Maraba and Simbi sectors located in Huye district, Southern province of Rwanda. The outreach was undertaken by health sciences students and involved the screening of hypertension, risk of diabetes, hepatitis, anemia, eye disease, and HIV. Methods: Clinical assessments and rapid laboratory diagnostic assays were used to screen invited residents from the two selected communities. An observation research was conducted from May 21 to 25 May, 2018, at Maraba and Simbi sector located in Huye district, Southern province, Rwanda. We employed a purposively sampling technique for participants’ recruitment in the outreach. The outreach was conducted as part teaching program and community engagement, and was endorsed by college of medicine and health sciences and all the subjects voluntarily participated in this exercise; the ethical approval was not applicable for this outreach activity. Results: The total beneficiaries from those sectors were 1427 citizens of whom females predominated at 72%. During the screening, hypertension was found to be high at 47.8% among adults. Anemia which mostly presumes iron deficiency was observed at 32.5% among under 15 years old children and at 15% in pregnant women. The vision impairment and cataract were observed at 5.66 and 19.59%, respectively. The assessed viral infection indicated a rate of 0.56% for HIV, 1.03% for HBV, and 7.17% for HCV. High blood glucose was found in 10.4% of the screened population. Conclusions: The findings highlight a high burden of non-communicable diseases (NCDs) in rural communities and call for further investigations and interventions to align with the sustainable development goals (SDGs), particularly access to affordable health services. Furthermore, the success of this outreach highlights the potential contribution of health care trainees in achieving these goals and calls for integration of such interventions in the health education curriculum.